Development of Digital Literacy Based Game Cards on Hydrocarbon Material - Eny Enawaty; Ira Lestari; Nadila; Fadhil Alwa Faridy; Rizki Furqanul Ichsan (Jurnal Penelitian Pendidikan IPA, 2025)
This research is motivated by the lack of learning media used in learning hydrocarbon material, so that student learning outcomes are not good. With the increasing development of digital technology in learning. Then it can be utilized in learning. Therefore, in this study, the researcher aims to develop digital literacy-based learning media in the form of game cards called Hy-Card cards so that learning is more enjoyable and learning outcomes are better. This study uses the ADDIE R&D model research method. The instruments used in this study were feasibility sheets and response questionnaires with a Likert scale. The results of the content feasibility test were obtained with an average of 98.5% (very feasible), the language was obtained with an average of 98% (very feasible), and the media was obtained with an average of 97% (very feasible). The results of the individual response trial obtained a result of 85% (very good), and the small group trial obtained an average of 89% (very good) and the large group trial obtained an average of 88% (very good). So, it can be concluded that the Hy-Card game card is very suitable for use in hydrocarbon learning with the average response trial obtaining very good results.